A modified dipole Quasi-Yagi antenna to increase directivity and gain for WLAN application - Hock G.T.; Hock G.C.; Ghafil S.F.; Chakrabarty C.; Ismail R. (Institute of Electrical and Electronics Engineers Inc., 2023)
WLAN network is the most popular wireless network used for various electronic devices to exchange data. Electronic devices such as smart phone, laptop, printer, digital camera and smart TV are using the Wi-Fi antenna to exchange data wirelessly. However most of the Wi-Fi antenna is isotropic antennas which transmit and receive Wi-Fi signal omnidirectional. According to current IEEE 802.11n standard, omnidirectional Wi-Fi antenna has limitation to reach 250m maximum due to its low directivity. In this paper, a Quasi-Yagi antenna has been built to enhance antenna gain and directivity. © 2014 IEEE.